2007
DOI: 10.1099/vir.0.82959-0
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus polymerase inhibits the interferon-inducible MyD88 promoter by blocking nuclear translocation of Stat1

Abstract: Previous studies have suggested that hepatitis B virus (HBV) blocks expression of the alpha interferon (IFN-a)-inducible myeloid differential primary response protein (MyD88) gene. To study the molecular mechanism(s) of the inhibition of MyD88 expression by HBV, MyD88 promoter reporter plasmids and vectors expressing different HBV viral proteins were constructed. Co-transfection experiments showed that IFN-induced MyD88 promoter activity was inhibited by HBV polymerase expression in a dose-dependent manner and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
65
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 27 publications
6
65
1
Order By: Relevance
“…There are multiple reports implicating HBV Pol in modulating the host innate immune response, but none of these reports indicate the involvement of the mitochondria in manifesting these effects of Pol. Specifically, HBV Pol has been reported to reduce the response to type I IFN signaling by blocking NF-B, IRF3, and Stat1 nuclear translocation (25,26,72). Further, RIG-I has been identified as a direct antiviral sensor for the Ep stem-loop on the pgRNA to repress HBV replication.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple reports implicating HBV Pol in modulating the host innate immune response, but none of these reports indicate the involvement of the mitochondria in manifesting these effects of Pol. Specifically, HBV Pol has been reported to reduce the response to type I IFN signaling by blocking NF-B, IRF3, and Stat1 nuclear translocation (25,26,72). Further, RIG-I has been identified as a direct antiviral sensor for the Ep stem-loop on the pgRNA to repress HBV replication.…”
Section: Discussionmentioning
confidence: 99%
“…For example, evidence has been obtained that the HBV polymerase can interfere with IRF-3 and IRF-7 signaling by binding to the RNA helicase DDX3 (Fig. 1) (Foster et al 1991;Christen et al 2007;Wu et al 2007;Wang and Ryu 2010;Yu et al 2010).…”
Section: Innate Immunity During Hbv Infection: Recognition Defect or mentioning
confidence: 99%
“…Luciferase assays were performed as described previously (50). For chloramphenicol acetyltransferase (CAT) assays, Huh7 cells were transfected with the indicated plasmids.…”
Section: Plasmids and Virusesmentioning
confidence: 99%
“…We and others have shown that MyD88 expression can be induced by IFN-␣ and that MyD88 has an antiviral activity against HBV in hepatoma cells that is mediated by nuclear factor B (NF-B) activation (12,25,51,52). To counteract its inhibition, the HBV polymerase dampens the activation of the MyD88 promoter by blocking the nuclear translocation of Stat1, thereby reducing IFN-␣-inducible MyD88 expression (50), further suggesting a critical role for MyD88 in antiviral activity against HBV. The aim of the present study was to further investigate the antiviral activity of MyD88 and the mechanism of action.…”
mentioning
confidence: 99%